Google scholar citations and the emergence of new actors in research evaluation - Cabezas-Clavijo, Álvaro; Torres-Salinas, Daniel (Anuario ThinkEPI, 2012)
Google scholar citations, a system aimed at researchers, attempts to outline researchers´ bibliometric profile, providing citation indicators and the h-index. We review other tools designed to measure visibility and academic impact on the web, such as Microsoft academic search and the new initiatives grouped under the label altmetrics or alternative indicators. Finally, we discuss how the appearance of Google scholar citations and other products may affect the two major sources of bibliometric data, ISI Web of science and Scopus, and how this can influence the evaluation of scientific research.